A highly sensitive electrochemical cytosensor based on a triple signal amplification strategy using both nanozyme and DNAzyme. Issue 5 (14th January 2022) - Liu, Jinxia; Liu, Xiaodi; Yang, Luxia; Cai, Aiting; Zhou, Xiaobo; Zhou, Chu; Li, Guo; Wang, Qi; Wu, Mingmin; Wu, Li; Ji, Haiwei; Qin, Yuling
Abstract : A triple signal amplification strategy with nanozymes, DNAzyme and an electron transfer medium was developed to improve cytosensing performance. Abstract : The development of a sensitive cytosensor is beneficial for the early diagnosis and treatment of cancer. Herein, highly sensitive cytosensing was achieved by applying triple signal amplification strategies with Fe3 O4 @Au nanozymes and DNAzyme hybrids as electrochemical nanoprobes and toluidine blue (Tb) as the electron transfer medium. The Fe3 O4 @Au nanocomposites not only acted as nanozymes with excellent catalytic performance towards H2 O2 reduction but also served as promising scaffolds to carry massive electroactive substances and DNA probes. The dual-functional DNA probes were designed with the sequence of hemin/G-quadruplex to serve as the DNAzyme and the sequence of aptamer to recognize cancer cells. Furthermore, Tb was also conjugated to the surface of the Fe3 O4 @Au nanohybrids, working as the electron transport medium to magnify the electrochemical response. With the above design, the Fe3 O4 @Au nanozymes and hemin/G-quadruplex DNAzyme efficiently co-catalyzed the reduction of H2 O2 to accelerate the electron transfer of Tb, which realized triple signal amplification and finally improved the performance of the electrochemical cytosensor. The proposed cytosensor achieved a sensitive detection of HepG2 cells with a low detection limit of 20 cells mL −1, and could be potentially used as an effective analysis tool in early cancer diagnosis in the future.